ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN - Tri Nurdyastuti; Dibyo Iskandar (JURNAL AKUNTANSI DAN INVESTASI, 2020)
The purpose of this study is to test and empirically prove the influence of the significance of profitability (ROA), liquidity (CR), solvency (DER) and disclosure (DISC) on the acceptance of going concern audit opinion. The population used in this study are all Food and Baverage companies on the Indonesia Stock Exchange.The sample selection technique uses purposive sampling. The analytical method used is logistic regression analysis. Based on the test results show that profitability and liquidity have a positive and not significant effect on going concern audit opinion, while solvency and disclosure have a negative effect not significant on going concern audit opinion. Negelkerke R Square value of 64.8% which means going concern audit opinion can be explained by an independent variable of 64.8% while the rest 35.2% is explained by other variables.